Evaluating Sentence Alignment on Croatian-English Parallel Corpora - Seljan, Sanja (Array, 2008)
This paper describes an experiment in applying sentence alignment methods to Croatian-English parallel corpora and systematically evaluate their performance within the recall, precision and F-measure framework. It is our primary goal to provide an insight and a reference point on sentence alignment accuracy for Croatian-English language pair and also to extend the scope of (Tadić, 2000) – to our knowledge, the first experiment dealing with sentence alignment of Croatian-English parallel corpora – by utilizing newly implemented tools, creating corpora subsets defined by genre and finally by expanding and formalizing its preliminary observations on alignment accuracy. Therefore, in this paper we start off by briefly describing and argumenting sentence alignment paradigms of choice and presenting available language resources, subset of Croatian-English parallel corpus described in (Tadić, 2000) being our primary asset. These descriptions are followed by a formal definition of our testing framework. Results are then discussed in detail and conclusions are stated along with a brief insight on possible future work.